A Generalized Equation for Prediction of VO2peak from a Step Test - Selland, Corey A.; Kelly, Joshua; Gums, Kathleen; Meendering, Jessica R.; Vukovich, Matt (International Journal of Sports Medicine, 2020)
This study aimed to develop an equation to reduce variability of VO2peak prediction from a step test and compare VO2peak prediction from the new equation to the Queen’s College Step Test (QCST). The development group (n=86; 21.7±2 years) was utilized to develop the SDState step test equation to predict relative VO2peak. The cross-validation group (n=99; 21.6±2 years) was used to determine the validity of the SDState step test VO2peak prediction equation. A regression analysis was used to identify the best model to predict VO2peak. Analysis of variance (ANOVA) was further used to determine differences among predicted and measured VO2peak values. Forward stepwise multiple regression identified age, sex, abdominal circumference, and active heart rate at the 3-min mark of the step test to be significant predictors of VO2peak (mL·kg−1·min−1). No differences among measured VO2peak (47.3±7.1 mL·kg−1·min−1) and predicted VO2peak (QCST, 46.9±9.3 mL·kg−1·min−1; SDState 48.3±5.7 mL·kg−1·min−1) were found. Pearson correlations, ICC, SEE, TEE, Bland-Altman plots, and Mountain plots indicate the SDState step test equation provides less variation in the prediction of VO2peak compared to the QCST. The SDState step test equation is effective for predicting VO2peak from the YMCA step test in young, healthy adults.
Keywords: fitness testing; cardiorespiratory fitness; exercise prescription; submaximal exercise